Os efeitos dos choques de política monetária sobre a atividade econômica e os preços no Brasil - Omoto, Kátia Harumi (2006)
The present study has as central objective to analyze the effects of the shocks of monetary policy on the level of economic activity and on the prices (inflation) in Brazil, using a new methodology, free from endogenous and anticipatory movements. Based in the model of ROMER & ROMER (2004), the analysis understands the period of July from 1996 to January of 2005. The results of this study indicate that the monetary policy in Brazil has been guided to combat the inflation. However, a restrictive shock of monetary policy has been affecting the production level much more than the prices of the economy. The negative response (reduction) of the production it begins soon after the increase of the interest rate and, the maximum effect happens approximately 15 months after the shock. However, in spite of the principal objective of the monetary policy to be the stability of prices, these response very a little to the monetary shocks. The country is getting to maintain certain stability of prices at the expense of a low economical growth, that in the long period can be reflected in an economic stagnation.